The Influence Of Electronic Word Of Mouth (E-Wom) And Price On The Purchase Intention Of Generation Zconsumers In The Tiktok Shop Marketplace - Anggun Ayu Lestari; Yudi Irawan Abi; Siti Hanila (Universitas Dehasen Bengkulu, 2026)
The rapid development of technology and information today has changed the way consumers shop. The convenience of accessing information through the internet allows consumers to find the products they need more easily. In this regard, TikTok Shop has become a very popular marketplace among Generation Z in Bengkulu City. The purpose of this study is to determine the effect of electronic word of mouth (e-WOM) and price on the purchase intention of Generation Z consumers in the TikTok Shop marketplace. The sample in this study consisted of 120 TikTok Shop users in Bengkulu City. Data were collected through questionnaires and analyzed using a quantitative approach. The results of the regression analysis show that the regression equation is: Y = 6.224 + 0.283X1 + 0.885X2 + e. Electronic word of mouth has a significant effect on the purchase intention of Generation Z consumers in the TikTok Shop marketplace, with a significance value of 0.021 < 0.05. Price also has a significant effect, with a significance value of 0.000 < 0.05. Both electronic word of mouth and price simultaneously have a significant effect on the purchase intention of Generation Z consumers in the TikTok Shop marketplace, with a significance value of 0.000 < 0.05. Based on the results of the study, it was found that the price variable (X2) has the greatest influence on the purchase intention of Generation Z consumers in the TikTok Shop marketplace. This indicates that consumers tend to be more attracted to prices that are more affordable compared to those in physical stores or other marketplaces.